PERSEPSI MAHASISWA TERHADAP FLEXING DAN PENGARUHNYA TERHADAP MINAT INVESTASI - Zahra, Muthia; Mira Amelia, Mira Amelia; Wahyuni, Putri; Septianti, Renata; Fauzany, Riffka (Jurnal Ekonomi Manajemen Bisnis Dan Akuntansi : EMBA, 2024)
Investment is the activity of investing capital into certain forms of assets so that the value of the assets is greater than when initially investing capital. Along with the rapid development of technology, investing has now become easier because stock investments can be done online. Flexing is a term used for those who like to show off their wealth. The existence of social media makes the flexing phenomenon even easier to do. This research uses quantitative methods. This research aims to find out whether there is an influence of flexing on investment interest made by students. The results of research on 44 students from on of the universities in Bandung show that there is a negative influence of flexing on investment interest, but is not significant at the 5% level. Student perceptions of flexing tend to have a negative impact, and students’ decisions regarding investment interest are driven more by other factors such as wise financial planning and management.